Analisis Free Body Diagrams pada Siswa SMA dalam Menyelesaikan Tes Uraian Terstruktur - Rahmaniar, Andinisa; Heni, Rusnayati; Asep, Sutiadi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2016)
Abstract Pre-study which was done by researcher got 66.76% students in one of high school in Garut district didn’t construct free body diagrams before completing physics problems particularly on the force matter. As a consequence, researcher has a purpose to analyze free body diagrams on high school students to solve restricted response items. The research method which was used is quantitative descriptive. Through purposive sampling technique, obtained a sample of 35 students in one of high school in Garut district. The instrument was used in this study is restricted response items so that students are directed to construct free body diagrams first before completing the test. The data obtained was processed with percentage descriptive analyses. Based on research conducted, there are three types of constructing free body diagrams. The first type, about 8.57% of students construct free body diagrams outside the object which is being observed, the second type as much as 62.85% students construct free body diagrams directly on the object which is being observed and the third type as much as 22.86% students construct free body diagrams outside and directly on the object which is being observed. Keywords: force, free body diagrams, restricted response items Abstrak Studi pendahuluan yang peneliti lakukan memperoleh 66,76% siswa di salah satu SMAN di Kabupaten Garut tidak menggambar free body diagrams sebelum menyelesaikan soal fisika khususnya pada materi gaya. Oleh karena itu, tujuan penelitian ini adalah untuk menganalisis free body diagrams pada siswa SMA dalam menyelesaikan tes uraian terstruktur. Metode penelitian yang digunakan yaitu kuantitatif deskriptif. Sampel diambil secara purposive sampling sebanyak 35 siswa di salah satu SMAN di Kabupaten Garut. Instrumen yang digunakan adalah tes bentuk uraian terstruktur, yang telah dikembangkan dalam pennelitian sebelumnya, yang diarahkan agar siswa menggambar free body diagrams sebelum menjawab tes secara keseluruhan. Data diolah menggunakan analisis deskriptif persentase. Hasil penelitian menginformasikan bahwa terdapat tiga tipe cara menggambar free body diagrams. Tipe pertama sebanyak 8,57% siswa menggambar free body diagrams di luar benda yang ditinjau, tipe kedua sebanyak 62,85% siswa menggambar free body diagrams langsung pada benda yang ditinjau dan tipe ketiga sebanyak 22,86% siswa menggambar free body diagrams di luar dan langsung pada benda yang ditinjau. Kata-Kata Kunci: gaya, free body diagrams, tes uraian terstruktur